Microelectronic circuit design - Jaeger, Richard C. (McGraw-Hill, 2008)
The book provides a comprehensive knowledge on the basic techniques of modern electronic circuit design, analog and digital, discrete and integrated. The content is divided into three main parts: solid state electronic and devides, digital electronics, analog circuit design